The Relationship between Intensity of Gadget Use and Speech and Language Development in Toddlers - Wa Ode Nurl Ainun Asgaf; Rauly Rahmadhani; Trisnawaty (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background : The alpha generation are those born after 2010, who are claimed to be the smartest generation because they were born and grew up in an era of rapid technological and internet development. So that we can find many toddlers who are familiar with gadgets. However, excessive use of gadgets will reduce toddler interaction with the environment and toddlers rarely communicate with people around them, this naturally disrupts the process of toddler speech and language development. Objective: This study aims to analyze the relationship between the intensity of gadget use and the development of speech and language aspects in toddlers in Wameo Village, Baubau City. Method: This study is an observational analytic type with a cross sectional approach. This study used 77 samples taken using purposive sampling technique which were then measured using a questionnaire. Result: The results showed that toddlers who used gadgets with mild intensity experienced normal speech and language development, 10.4% of toddlers who used gadgets with moderate intensity experienced delays, and 33.8% who used gadgets with severe intensity experienced delays. Hypothesis testing using the Chi-Square Test obtained a p-velue value of 0.000 (P <0.05). Conclusion: In conclusion, there is a significant relationship between the intensity of gadget use and delayed speech and language development in toddlers in Wameo Village, Baubau City.